2011
DOI: 10.4081/ijfs.2011.1s.149
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic Amine Content in “Pecorino Del Parco Di Migliarino - San Rossore”

Abstract: Biogenic amines (BAs) can be naturally present in several foods. They are mainly produced in large amounts by amino acid decarboxylases activity of bacteria. The BAs content has been associated to the quality of raw material and to fermentation or spoilage processes. The aim of the present study was to asses the content of BAs (single and total value) in the core and in the external part of a Tuscan traditional pecorino cheese. Sixteen “Pecorino del Parco di Migliarino-San Rossore” cheeses belongin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Despite the high levels of BA, HI, the BA mainly responsible of intoxication cases, was detected in very limited amounts in RC samples or not detected at all in all the other samples. These data are in agreement with those reported for other Italian ewes' milk cheeses (Forzale et al, 2011a;Lanciotti et al, 2007;Mascaro et al, 2010;Schirone et al, 2011;Torracca et al, 2015), although higher levels have been found in ewes' milk cheeses both in Italy (Martuscelli et al, 2005) and in other countries (Fernández-García, Tomillo, & Núñez, 1999;Pinho, Ferreira, Mendes, Oliveira, & Ferreira, 2001).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Despite the high levels of BA, HI, the BA mainly responsible of intoxication cases, was detected in very limited amounts in RC samples or not detected at all in all the other samples. These data are in agreement with those reported for other Italian ewes' milk cheeses (Forzale et al, 2011a;Lanciotti et al, 2007;Mascaro et al, 2010;Schirone et al, 2011;Torracca et al, 2015), although higher levels have been found in ewes' milk cheeses both in Italy (Martuscelli et al, 2005) and in other countries (Fernández-García, Tomillo, & Núñez, 1999;Pinho, Ferreira, Mendes, Oliveira, & Ferreira, 2001).…”
Section: Discussionsupporting
confidence: 92%
“…The ripening process also influences BA levels in cheeses, since the proteolysis that takes place during this period increases the availability of amino acids, which can then undergo decarboxylation mediated by microbial enzymes (Novella-Rodríguez et al, 2003). Many studies on the evolution of the BA profile during the ripening of cheese have shown that BA content increases during this period (Fernández et al, 2007;Forzale et al, 2011a;Galgano et al, 2001;Komprda et al, 2008;Lanciotti et al, 2007;Martuscelli et al, 2005;Novella-Rodríguez et al, 2003;Novella-Rodríguez, Veciana-Nogués, Trujillo-Mesa, & Vidal-Carou, 2002;Pinho et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of relevant amounts of BA in cheeses has been recently documented for a few types of Pecorino cheeses (Martuscelli et al, 2005 ; Lanciotti et al, 2007 ; Del Signore and Di Giacomo, 2008 ; Mascaro et al, 2010 ; Mercogliano et al, 2010 ; Bavazzano et al, 2011 ; Forzale et al, 2011 ; Schirone et al, 2011 ). In these studies the quantitative and qualitative accumulation of such compounds was extremely variable (Table 4 ).…”
Section: Biogenic Amines In Pecorino Cheesesmentioning
confidence: 89%
“…Despite the good hygienic quality of milk and the use of selected starter culture, BAs may still be formed, and sometimes at relatively high levels, in dairy products, especially in cheeses relying on the natural microbiota for fermentation and/or ripening (Forzale and others ; Schirone and others ). In addition, BAs may be formed from sources other than starter cultures or bacterial contaminants, such as yeasts and molds used as a secondary microbiota, or may be naturally present in milk, such as spermine, spermidine, putrescine, and PEA (Gloria and others ).…”
Section: Biosynthesis Pathways Of Basmentioning
confidence: 99%